Transpulmonary amino acid metabolism in the sugen hypoxia model of pulmonary hypertension. (1st March 2023) - Philip, Nicolas; Pi, Hongyang; Gadkari, Mahin; Yun, Xin; Huetsch, John; Zhang, Cissy; Harlan, Robert; Roux, Aurelie; Graham, David; Shimoda, Larissa; Le, Anne; Visovatti, Scott; et al.
Abstract: In pulmonary artery hypertension (PAH), emerging evidence suggests that metabolic abnormalities may be contributing to cellular dysfunction in PAH. Metabolic abnormalities such as glycolytic shift have been observed intracellularly in several cell types in PAH, including microvacular endothelial cells (MVECs). Concurrently, metabolomics of human PAH samples has also revealed a variety of metabolic abnormalities; however the relationship between the intracellular metabolic abnormalities and the serum metabolome in PAH remains under investigation. In this study, we utilize the sugen/hypoxia (SuHx) rodent model of PAH to examine the RV, LV and MVEC intracellular metabolome (using targeted metabolomics) in normoxic and SuHx rats. We additionally validate key findings from our metabolomics experiments with data obtained from cell culture of normoxic and SuHx MVECs, as well as metabolomics of human serum samples from two different PAH patient cohorts. Taken together, our data, spanning rat serum, human serum and primary isolated rat MVECs reveal that: (1) key classes of amino acids (specifically, branched chain amino acids—BCAA) are lower in the pre‐capillary (i.e., RV) serum of SuHx rats (and humans); (2) intracellular amino acid levels (in particular BCAAs) are increased in SuHx‐MVECs; (3) there may be secretion rather than utilization of amino acids across the pulmonary microvasculature in PAH and (4) an oxidized glutathione gradient is present across the pulmonary vasculature, suggesting a novel fate for increased glutamine uptake (i.e., as a source of glutathione). in MVECs in PAH. In summary, these data reveal new insight into the shifts in amino acid metabolism occurring across the pulmonary circulation in PAH.